2015
DOI: 10.4236/ajps.2015.65065
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Selected Plant Extracts against <i>Pyricularia grisea</i>, Causal Agent of Rice Blast Disease

Abstract: Rice blast disease, caused by a seed-borne fungus Pyricularia grisea, is an important and serious disease of rice (Oryza sativa L.) worldwide. The disease has been reported to cause yield losses of up to 40% in Tanzania. Studies were conducted to determine the effect of aqueous extracts of Aloe vera, Allium sativum, Annona muricata, Azadirachta indica, Bidens pilosa, Camellia sinensis, Chrysanthemum coccineum, processed Coffee arabica, Datura stramonium, Nicotiana tabacum and Zingiber officinalis for control o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 7 publications
2
36
0
5
Order By: Relevance
“…The use of plant extracts to control the infestation of fungi on rice was potent and environmentally friendly compared with synthetic fungicides [21]. In a previous work, Hubert et al [8] reported that aqueous extracts of Coffee arabica at 10% and 25% (v/v) exhibited 81.12 and 89.40% inhibition on P. grisea, respectively. Suriani et al [22] documented that the crude extract of Piper canium inhibited mycelial growth of P. grisea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of plant extracts to control the infestation of fungi on rice was potent and environmentally friendly compared with synthetic fungicides [21]. In a previous work, Hubert et al [8] reported that aqueous extracts of Coffee arabica at 10% and 25% (v/v) exhibited 81.12 and 89.40% inhibition on P. grisea, respectively. Suriani et al [22] documented that the crude extract of Piper canium inhibited mycelial growth of P. grisea.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, extracts from E. aromatica, P. guineense, and G. kola could serve as bio-fungicides against the growth of P. grisea [7]. Several other plants have been tested and showed significant results against P. grisea [7][8][9]. However, the application of plant extracts in agricultural practice is labor-intensive and costly.…”
Section: Introductionmentioning
confidence: 99%
“…Gohel and Chauhan (2015) reported that Neem leaf extract were found effective but comparably less significant than standard fungicides and bio-agent in minimizing leaf blast intensity in rice. Hubert et al, (2015) observed that extracts from C.arabica, N. tabacum, A. vera, A. indica, were found significant to manage rice blast disease in-vitro and in-vivo.…”
Section: Leaf Extract Of Adhatoda Vasica Andmentioning
confidence: 99%
“…The solvents utilized for the extraction are ethanol (100%), methanol (100%) and hot water. A slightly modified method of Hubert et al (2015) was adopted for the extraction processes. Precisely, one hundred grams (100 g) of the fine powered leaf was weighed using a weighing balance (A&D, UK); this weighed sample was immersed in 200 ml of each of the above mentioned solvents contained in three different carefully labeled conical flasks, to obtain three different extracts, which were accompanied by vigorous shaking for five (5) minutes and thereafter allowed to remain on the rotating shaker for 24 hours.…”
Section: Preparation Of the Leaf Extractsmentioning
confidence: 99%